Pengaruh Akuntabilitas dan Transparansi Dana Desa Terhadap Kualitas Laporan Keuangan Desa : Studi Pada Desa Pematang Lingkung, Kecamatan Batang Merangin, Kabupaten Kerinci - Sukma Gusti Armaida; Usdeldi Usdeldi; Erwin Saputra Siregar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine the effect of accountability and transparency of village funds on the quality of village financial reports in Pematang Lingkung Village, Batang Merangin District, Kerinci Regency. This research uses quantitative methods with a descriptive approach, data collection techniques using questionnaires and the sample in this research was 30 village officials and members of institutional organizations in Pematang Lingkung Village, Bapatang Merangin District, Kerinci Regency. The technique for determining the sample is to use a saturated sample by taking the entire population as the research sample. Data analysis using descriptive statistics, research instrument testing, classical assumption testing, multiple linear regression analysis and hypothesis testing. The results of this research partially show that the Accountability variable (X1) with a significance value of 0.143 > 0.05 and tcount of -1.509 <ttable 1.697 states that accountability has no effect on the quality of financial reports, the transparency variable (X2) with a significance value of 0.514 > 0.05 and tcount of 3.501 > ttable 1.697 states that the transparency variable has a significant effect on the quality of financial reports. Meanwhile, simultaneously with the value that Fcount is 6.789 > Ftable 2.96 and a significance of 0.04 <0.05 states that accountability and transparency of village funds has a positive and significant effect on the quality of financial reports in Pematang Lingkung Village, Batang Merangin District, Kerinci Regency.